2003
DOI: 10.1103/physrevb.67.195326
|View full text |Cite
|
Sign up to set email alerts
|

Overlap effects on electron transmission through doped molecular wires

Abstract: The electron transmission properties of a molecular wire, containing a single impurity, are investigated in the context of the tight-binding approximation. The inclusion of overlap gives rise to nonorthogonal orbitals, whose treatment requires a tensorial formalism to obtain the Green function arising in the Lippmann-Schwinger equation approach to the transmission probability T(E). The presence of overlap has profound effects on the T(E) curves. In particular, two antiresonances appear, which are governed by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Because of its fundamental interest and practical importance, electronic transport in onedimensional structures with a wide variety of geometries has been intensely investigated in the recent past. These studies include quantum conductance in one-dimensional mesoscopic rings [173,174], the transmission zeros and poles in quantum wave-guides [175][176][177][178][179], the transmission in coupled quantum wires [180][181][182][183][184], the size-effect on conductance in ballistic quantum wires [185], the electronic stop bands [186][187][188], the electron channel drop tunneling [189][190][191], the localization effects [192], the overlap effects on electron transmission through molecular wires [193][194][195], the transmission through two-dimensional lattices [196], . .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its fundamental interest and practical importance, electronic transport in onedimensional structures with a wide variety of geometries has been intensely investigated in the recent past. These studies include quantum conductance in one-dimensional mesoscopic rings [173,174], the transmission zeros and poles in quantum wave-guides [175][176][177][178][179], the transmission in coupled quantum wires [180][181][182][183][184], the size-effect on conductance in ballistic quantum wires [185], the electronic stop bands [186][187][188], the electron channel drop tunneling [189][190][191], the localization effects [192], the overlap effects on electron transmission through molecular wires [193][194][195], the transmission through two-dimensional lattices [196], . .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Here we provide simple arguments why equivalent OB and NOB sets yield the same transmission when the overlap is taken into account in the way discussed by Emberly and Kirczenow (EK). 4,10 We demonstrate by simple calculations how we get the exact results for transmission also when Eq.…”
Section: Introductionmentioning
confidence: 91%
“…fc i ; c j g5fc j ; c i g50; (10) and the operators c i (c † i ) create (annihilate) the state jw i i5S ij jw i i, with the remaining anti-commutators fc i ; c j † g5S ij ; fc i ; c j g5fc i † ; c j † g50;…”
Section: Nonorthogonal Basis Set Field Operator Expansionmentioning
confidence: 99%
“…In the time-dependent (TD) case, a number of studies have demonstrated that the exact treatment of nonorthogonality (i.e., the use of a nonorthogonal basis without any transformations) in electronic transport is necessary for reliable results. [3][4][5][6][7][8][9][10][11] Since the early days of molecular orbital theory, there was a strong and prominent advocacy that nonorthogonality is not just a mathematical convenience. [12][13][14][15][16][17] The nonorthogonality of atomic orbital basis sets in electronic transport theories is typically handled via L€ owdin [18] or lead-device orthogonalization.…”
Section: Introductionmentioning
confidence: 99%